Cross-Species Amplification and Variability of Microsatellite DNA Markers in Domesticated Indonesian Mahseer; A Case Study with Tor soro, Tor douronensis and their Interspecific Hybrids - Imron Imron; Agung Asrori; Khotibul Umam; Otong Zenal Arifin; Dessy Nurul Astuti (HAYATI Journal of Biosciences, 2022)
Indonesian mahseer (Tor spp.) are freshwater species of high economic, cultural, and conservatory values. Owing to their high values and environmental degradation, the population of Tor fish gradually decreased, and domestication efforts have been made to conserve the population. This study was aimed to assess the cross-species amplification and microsatellite genetic diversity in Indonesian mahseer Tor soro (SS), Tor douronensis (DD), and their interspecific hybrids using primers developed for Tor putitora. Eleven primer sets were used to test for amplifiability and screen genetic diversity in 40 progenies derived from those three groups. Results showed that seven primer sets (64%) successfully amplified loci. Genetic screening using the three most consistently amplifying primers showed that the number of alleles in the three populations was low, ranging from 2 to 5 alleles. The observed heterozygosity (HO) was high ranging from 0.650 to 0.789, and the fixation index (FIS) was negative, indicating heterozygosity excess. In line with other parameters, the P-values of the HW parameter of several loci-population combinations were significantly departed from equilibrium (P <0.05). A few private alleles were observed in parental line DD and the hybrids. Overall, the cross-species primers developed from T. putitora were able to amplify loci in T. soro, T. douronensis and their hybrids and genetic diversity in the hybrid population was slightly higher than those in parental lines. Possible factors driving the phenomena and practical implications of these findings on the conservation measures are discussed.